Technological intensity patterns and job polarization in Brazil's manufacturing industry - Rocha, Gabriella Rodrigues [UNESP] (2024)
Although studies on the innovation-employment nexus are longstanding in economics, current investigations are focused on the effects of digital technologies on the labor market. This paper examines how technological intensity affects job polarization in Brazil's manufacturing industry. Utilizing the technological standardization methodology by Galindo-Rueda and Verger (2016), data were grouped using the Fisher-Jenks algorithm at the two-digit sectoral (2013) was employed. A pattern of production concentration in sectors with lower innovation relative to value added can be observed. According to the RTI, employment in the industry sectors is polarized; however, the hypothesis that higher technological intensity leads to greater job polarization was not observed in some sectors of the Brazilian manufacturing industry.